The Impact of Fathers on Children’s Well-Being - Sarah M. Ellis; Yasmin S. Khan; Victor W. Harris; Ricki McWilliams; Diana Converse (EDIS)
American families have changed dramatically over the last century. Currently, about half the children in the United States will live apart from their fathers some time during their childhood because their parents have separated and the proportion of births to unmarried women has risen from 5 percent in 1960 to 41 percent in 2011. But a father who is absent from the household may not necessarily be absent from his child’s life. This 5-page fact sheet provides a brief summary of the history of fatherhood in America and discusses the importance of involved fathers, and how mothers, other family members, and adult role models can make a positive impact in a child’s life. Written by Sarah M. Ellis, Yasmin S. Khan, Victor W. Harris, Ricki McWilliams, and Diana Converse, and published by the UF Department of Family, Youth and Community Sciences, October 2014.